Fire Suppression Simulation Application Development Stereo Graphics Based (Virtual Reality) - Windarko Windarko (West Science Information System and Technology, 2023)
Modern man today is very dependent on his life with computers. Because with the help of computer technology can ease their task. A computer can create a situation similar to the original. This technology is commonly called simulation. Serious simulations depict a system that is difficult to perform in the real world and is at high risk. These serious simulations are usually much more developed in the making. This development technology is called Virtual Reality (VR). Virtual Reality (VR) is a development of stereo display techniques. Where users can see an object with dimensional depth that will give a 3D effect on the human brain. Based on the background above, the author tries to implement stereo displays in firefighting simulation (FFS) applications. The simulation engine used is Open Scene Graph with Microsoft Visual Studio 2008 compiler, which uses the C++ programming language. The GUI display design uses Qt 4.7.3. Users will try the stereo display effect in the FFS application and interact between the fire particle system and the water particle system to compare factors that cause fire particle system outages. Of all the implementations and trials carried out, the author succeeded in implementing stereoscopic fire suppression simulation applications. Because all objects in this application already have a red shadow for the left side of the thing and a blue shadow for the right side. The interaction between the user and the fire suppression simulation application was also successfully displayed in this Fire Fighting Simulation (FFS) application. The fire particle system will be extinguished if the user performs fire suppression interactions.